Long-term efficacy and patient satisfaction of pulsed radiofrequency therapy in temporomandibular disorders: A randomized controlled trial. Issue 52 (30th December 2021) - Jo, Jung Hwan; Jang, Yewon; Chung, Gehoon; Chung, Jin Woo; Park, Ji Woon
Abstract: Background: Pulse radiofrequency (PRF) therapy is one of effective physical therapy modalities for treat temporomandibular disorders (TMD). This prospective randomized controlled trial aimed to evaluate the long-term treatment efficacy and patient satisfaction with PRF therapy in TMD. Methods: Eighty-six female patients with TMD were randomly assigned to either pulsed radiofrequency or placebo therapy in combination with other conventional treatments once a week for 12 weeks. A final analysis was performed 12 weeks after the completion of treatment. Clinical parameters and patient satisfaction were analyzed at baseline, 4, 8, and 12 weeks of intervention and at 24 weeks from baseline. Results: Pain intensity, comfortable and maximum mouth opening, and pain on capsule and masticatory muscle palpation were significantly improved after treatment in both groups. Notably, the pulsed radiofrequency group showed a significantly lower pain intensity at the final evaluation performed 3 months after the completion of treatment. Significantly more patients reported subjective pain improvement and satisfaction with treatment following intervention at baseline in the PRF group. Most patients did not report any discomfort following treatment in either group. However, significantly more patients in the PRF group reported a burning sensation with intervention. Conclusion: Long-term regular pulsed radiofrequency therapy was effective in significantly reducing TMD pain, and the effect was long-lasting following treatment completion. Pulsed radiofrequency therapy should be considered as a supportive physical therapy modality for TMD.